2020
DOI: 10.1002/star.202000151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Sodium Carboxymethyl Starch‐Graft Acrylamide/1‐Vinyl‐2‐Pyrrolidone Copolymers via Central Composite Design and Using as Filtration Loss Agent in Drilling Muds

Abstract: A graft copolymer is synthesized with graft copolymerization of acrylamide (AM) and 1‐vinyl‐2‐pyrrolidone (NVP) grafting onto sodium carboxymethyl starch (CMS) via central composite design (CCD). The initiation system consists of potassium persulfate (KPS) and sodium hydrogen sulfite (SBS). The copolymer is confirmed by infrared spectroscopy, nuclear magnetic resonance hydrogen spectroscopy, scanning electron microscopy, thermogravimetric experiment, and elemental analysis. The rheological performance, filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The FT-IR spectrum analysis of the SAANM is presented in figure 2. The spectrum exhibited characteristic absorption peaks of the -OH group in the main chain of the starch and the stretching vibrations of N-H in amide groups at 3327 cm −1 [49]. Additionally, the peak at 2930 cm −1 corresponded to the characteristic vibration absorption peak of C-H on the backbone of the polymer molecule, and 1016 cm −1 was attributed to the asymmetric stretching vibration of C-O-C in starch [49].…”
Section: Ft-ir Analysis Of Saanmmentioning
confidence: 99%
“…The FT-IR spectrum analysis of the SAANM is presented in figure 2. The spectrum exhibited characteristic absorption peaks of the -OH group in the main chain of the starch and the stretching vibrations of N-H in amide groups at 3327 cm −1 [49]. Additionally, the peak at 2930 cm −1 corresponded to the characteristic vibration absorption peak of C-H on the backbone of the polymer molecule, and 1016 cm −1 was attributed to the asymmetric stretching vibration of C-O-C in starch [49].…”
Section: Ft-ir Analysis Of Saanmmentioning
confidence: 99%
“…Results show that the product has the most excellent performance in reducing filtration volume, and the rheological performance is similar to that of CMS and better than CMC-LVT. 21 A graft copolymer KH570-AM-starch is synthesized by cassava starch (CSt), AM, and γ-methacryloxypropyl trimethoxysilane (KH570) that can be used as a fluid loss agent at 140 °C. 28 It is worth noting that KH570-AM-starch must be compounded with other agents to achieve a temperature resistance of 180 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that modification is an effective method to improve or obtain polymers. Some modified polymers have been used as high-performance treatment agents. For instance, Xiaodong Bai et al. graft acrylamide (AM) and 1-vinyl-2-pyrrolidone (NVP) onto sodium carboxymethyl starch (CMS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification could affect the crystallinity, morphology, thermal stability, and hydrophobicity of the starch. Therefore, physical, chemical, enzymatic, or dual modifications are the promising approaches for developing new products, retaining petrochemical resources and enhancing specific starch properties [ 12 ]. Chemical modification is the most widely accepted approach and contributes to the emergence of new functionality to the starch.…”
Section: Introductionmentioning
confidence: 99%